Effect of ozone of healing wounds after tooth extraction - Barylo, О.; Kanishyna, Т. (Actual Dentistry, 2018)
The aim: in an experiment on laboratory rats to study the the effect of ozone on the processes tissue regeneration after delet a tooth. To examine the effect of ozone on tissues regeneration during the experiment on rats. Materials and Methods. The set of experiments on 20 rats of both sex at the age of 12 to 22 months, having the weight of 180 to 220 g. The animals have been divided into the control group of 10 rats and the experimental group of 10 rats. For modeling an experimental pathological process for animals remove the corner tooth on the upper jaw, animals experimental group. In the control group used ozone therapy for the aim improvement of regeneration processes in a post-extraction wound. The result of the experiment was evaluated on the 3rd, 7th, 14th days. Results. In the microscopic study of granulation tissue revealed differences in its structure between the control and experimental groups. In the control group determined a significantly better morphometric dynamics indicator. Conclusions. Morphological study histological examinations the tissue, formed in the tooth post after it is removed, points out, that use ozone led to an activation of angiogenesis, reduction of inflammatory cell infiltration, activation of epithelization of post-extraction wounds after tooth extraction. Key words: rat, regeneration, experiment, ozone therapy.